2015
DOI: 10.1021/acs.bioconjchem.5b00406
|View full text |Cite
|
Sign up to set email alerts
|

PNA–Rose Bengal Conjugates as Efficient DNA Photomodulators

Abstract: Selective photoinduced modulation of DNA may provide a powerful therapeutic tool allowing spatial and temporal control of the photochemical reaction. We have explored the photoreactivity of peptide nucleic acid (PNA) conjugates that were conjugated to a highly potent photosensitizer, Rose Bengal (RB). In addition, a short PEGylated peptide (K-PEG8-K) was conjugated to the C-terminus of the PNA to improve its water solubility. A short irradiation (visible light) of PNA conjugates with a synthetic DNA resulted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…In 2015, Wang and co-workers incorporated a pentafluoroazobenzene-based click amino acid (F−PSCaa, 360) into calmodulin (CaM), a calcium-binding messenger protein, in E. coli via genetic code expansion (Scheme 104). 623 Following expression of the functionalized protein, F−PSCaa (360) reacted with a strategically placed cysteine residue to generate the azobenzene bridge in situ without any further treatment. The resultant bridge was reversibly switched between its trans and cis isomers using green and blue light, respectively.…”
Section: Photoswitchingmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2015, Wang and co-workers incorporated a pentafluoroazobenzene-based click amino acid (F−PSCaa, 360) into calmodulin (CaM), a calcium-binding messenger protein, in E. coli via genetic code expansion (Scheme 104). 623 Following expression of the functionalized protein, F−PSCaa (360) reacted with a strategically placed cysteine residue to generate the azobenzene bridge in situ without any further treatment. The resultant bridge was reversibly switched between its trans and cis isomers using green and blue light, respectively.…”
Section: Photoswitchingmentioning
confidence: 99%
“…Shemesh and Yavin reported an approach to target cross-linking to specific DNA sequences (Scheme ). Using a 10-mer peptide nucleic acid (PNA) modified with rose bengal ( 44 ) at the N-terminus and a C-terminal PEG 8 -spaced bis­(lysine) unit (K-PEG 8 -K), they observed relatively poor hybridization with a complementary ssDNA sequence. Nevertheless, monitoring the reaction under irradiation with polyacrylamide gel electrophoresis showed that the target ssDNA band was reduced as a new nonmigrating residue accumulated in the wells.…”
Section: Modification Of Innate Functionalitiesmentioning
confidence: 99%
“…For example, the photoreactive peptide nucleic acid (PNA) can be used to conjugate the PS Rose Bengal (RB) with PNA–RB, which exhibits sequence specificity, cell permeability, and photoactivation in the visible region. PNA–RB conjugates with synthetic DNA show enhanced photoactivity and support the involvement of 1 O 2 and may provide useful approach for selective PDT [ 102 ]. Moreover, the encapsulation of PSs into PEG is conducive for enhancing phototoxicity.…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…Yavin and colleagues proposed an alternative approach to the strategies illustrated above. Taking advantage of the high sensitivity of guanine towards 1 O 2 -mediated photo-oxidation, they synthesized peptide nucleic acids (PNAs) bearing a strong PS (RB) on a complementary G-rich DNA target [ 185 ]. The group illustrated the possibility to selectively induce oxidation of the target strand, with the subsequent formation of ICL products, presumably due to the reaction of 8-oxo-dG with the nucleophilic lysine introduced on the PNA strand (as described above in Section 2.2 ) [ 63 , 186 ].…”
Section: 1 O 2 In Bioorganic Chemistry Ap...mentioning
confidence: 99%
“…An example can be found in the use of synthetic probes complementary to an oligonucleotide target, decorated with a PS. A valuable example is reported by the Yavin group (see above Section 3.2 ), in which PNA probes, decorated with RB, could effectively and selectively target the DNA of choice [ 185 ]. Several methodologies featuring the conjugation of PS to oligonucleotides and analogues were reported in the literature, exploiting the principle of selective recognition to limit ROS generation to the targeted strand, leading to high levels of selectivity.…”
Section: How To Tame the Bulletmentioning
confidence: 99%